Breath–Body–Mind Core Techniques to Manage Medical Student Stress - Patricia L Gerbarg; Yaidy L Cruz-Cordero; Vincent A Conte; Martha E García; Angel Braña; Estela S Estape; Richard P Brown (Journal of Medical Education and Curricular Development, 2023)
Objectives This pilot study evaluated the feasibility of a live, interactive, synchronous, online, manualized intervention, Breath–Body–Mind Introductory Course (BBM-IC), for medical students. BBM-IC includes breathing, movement, and attention-focus techniques for stress management and better emotion regulation, energy, sleep, and mental focus. Methods Medical students attending a 2-h BBM demonstration were invited to participate in the 12-h BBM-IC and weekly 45-min 6-week group practice. Measures were obtained using Survey Monkey: patient health questionnaire (PHQ9), generalized anxiety disorder-7 (GAD-7), exercise-induced feeling inventory (EFI), sleep quality scale (SQS), and body perception questionnaire-short form (BPQ-SF) at pre-BBM-IC (T1), post-BBM-IC (T2), and 6 weeks post (T3). Perceived stress scale (PSS) and meditation practices questionnaire (MPQ) were measured at baseline (T1) only. Results Twelve medical students participated in BBM-IC 4-h daily for 3 days. Six attended practice sessions and completed 6-week post-tests. Mean scores comparison identified two variable sets with significant improvements: EFI tranquility ( p  < .005) and supradiaphragmatic reactivity ( p  < .040). Two measures reached near significance: SQS ( p  ≤ .060) and PHQ9 ( p  ≤ .078). Conclusion This pilot study provided preliminary evidence that BBM-IC may reduce stress and anxiety symptoms while improving mood, energy, mental focus, and other correlates of psychophysiological state in medical students. Taking time for self-care is challenging for medical students, as reflected in the small study enrollment. Designating time for BBM as a requirement within the medical curriculum would probably enable more students to participate and acquire skills to reduce the effects of stress on their physical and psychological health, as well as the health of their patients.